Teachers and ICT skills: towards a new digital Iiteracy - Meirinhos, Manuel (2014)
The information society, as an organizing paradigm of our society, is based on a vision of a gIobalized society, supported by the development of the Infonnation and Communication TechnoIogies (ICT).